Research on thermal performance improvement of lightweight buildings by integrating with phase change material under different climate conditions. (17th February 2017) - Li, Yanru; Wang, Yan; Meng, Xi; Zhang, Wei; Long, Enshen
Abstract : The application of a lightweight building is limited because its indoor temperature is highly affected by the outdoor environment due to the low thermal inertia of the lightweight envelope. In order to improve the thermal performance, this study focuses on lightweight buildings integrated with phase change materials. EnergyPlus software with building model validated by experimental data is used to analyze the thermal performance improvement of lightweight buildings by integrating with phase change materials under typical weather conditions in five climate zones in China. The results show that phase change materials can reduce temperature fluctuations through improving the heat stability of the lightweight envelope. Phase change materials can effectively improve the indoor thermal environment throughout the whole year in a temperate zone. Also, phase change materials can improve the indoor thermal environment of lightweight buildings significantly in the transition seasons, but it also reduces the hours of the indoor air temperature within the range 18°C (64.4°F) to 26°C (78.8°F) during cold winters and hot summers. For the lightweight buildings with air conditioning, due to the addition phase change material, heating loads can be reduced by 40–70%, while cooling loads increase slightly in the summers with the higher air temperature.